2021
DOI: 10.1002/jpen.2116
|View full text |Cite
|
Sign up to set email alerts
|

Admission factors associated with nutritional status deterioration and prolonged pediatric intensive care unit stay in critically ill children: PICU‐ScREEN multicenter study

Abstract: Background Early identification of patients in the pediatric intensive care unit (PICU) at risk of nutritional status (NS) deterioration and poor outcomes is desirable. We aimed to identify factors associated with NS deterioration and prolonged PICU stay. Methods Prospective cohort study in eight Brazilian PICUs with children <18 years with a PICU stay >72h. We used multivariable logistic regression to identify the clinical, laboratory, and nutrition variables at admission that were associated with outcomes. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Ventura et al 27 found an association with complex chronic conditions, age of <2 years, fluid overload and hypoalbuminemia at admission, and prolonged PICU stays. 27 To address this concern, they developed and trialed a nutrition risk screen for this population. This screen is, in a broader sense, a nutrition risk screen vs a malnutrition risk screen.…”
Section: Icu Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ventura et al 27 found an association with complex chronic conditions, age of <2 years, fluid overload and hypoalbuminemia at admission, and prolonged PICU stays. 27 To address this concern, they developed and trialed a nutrition risk screen for this population. This screen is, in a broader sense, a nutrition risk screen vs a malnutrition risk screen.…”
Section: Icu Settingmentioning
confidence: 99%
“…Patients in the pediatric ICU (PICU) need early identification for risk of NS deterioration. Ventura et al 27 found an association with complex chronic conditions, age of <2 years, fluid overload and hypoalbuminemia at admission, and prolonged PICU stays 27 . To address this concern, they developed and trialed a nutrition risk screen for this population.…”
Section: Icu Settingmentioning
confidence: 99%
“…The evidence of malnutrition correlation with COVID-19 outcomes in the pediatric population is very scarce, but it is well established that malnutrition is associated with poor outcomes including longer hospital stay, longer mechanical support, and overall higher risk of mortality [ 55 58 ]. Several studies have reported that children with comorbidities including obesity are at greater risk of developing symptomatic illness or requiring admission to the hospital [ 59 , 60 ].…”
Section: Covid-19 Disease and Mortalitymentioning
confidence: 99%
“…The prevalence of malnutrition, specifically undernutrition, in hospitalized children has been reported to be between 6% and 51%, with vulnerable populations, such as children with critical illness, experiencing further nutrition deterioration and poor outcomes during their hospital stay. 1,2 Clinical outcomes specific to hospitalized children who are undernourished include longer hospital stay, 3,4 higher rates of infections, 5 and greater healthcare costs. 6 The additional in-hospital costs associated with malnutrition have been estimated to be three times higher in a US-based study 4 and 80 million euros per year in a European study of hospitalized children with malnutrition.…”
mentioning
confidence: 99%
“…The challenges facing patients on either end of this spectrum of malnutrition can be quite diverse. The prevalence of malnutrition, specifically undernutrition, in hospitalized children has been reported to be between 6% and 51%, with vulnerable populations, such as children with critical illness, experiencing further nutrition deterioration and poor outcomes during their hospital stay 1,2 . Clinical outcomes specific to hospitalized children who are undernourished include longer hospital stay, 3,4 higher rates of infections, 5 and greater healthcare costs 6 .…”
mentioning
confidence: 99%